Rational Design of Hemicyanine Langmuir Monolayers by Cation-Induced Preorganization of Their Structure for Sensory Response Enhancement - Shokurov, A V (Langmuir : the ACS journal of surfaces and colloids, 2018)
This study takes a novel approach to the enhancement of receptor properties of thin-film sensors based on hemicyanine dyes with dithia-aza-crown-ionophoric moiety. By means of in situ UV-vis and X-ray reflectivity (XRR) measurements, it was revealed that the introduction of up to 0.25 mmol of Hg2+ under a preliminarily compressed monolayer, formed on pure water, does not lead to cation binding. This is due to the formation of "head-to-tail" aggregates (H-type), in which ionophoric group is blocked by the neighboring molecule. However, the presence of barium cations in the subphase under the forming Langmuir monolayer of the mentioned compound causes codirectional (head-to-head) orientation of chromoionophore fragments. This provides preorganization of a monolayer structure that facilitates the binding of complementary mercury cations, even in a compressed state: asymmetric sandwich complexes containing two dye molecules coordinate a Hg2+ cation between them. This complex structure was confirmed by molecular modeling based on the electron density distribution calculated from XRR measurement data. Such preorganization of supramolecular ensembles induced by cations, which do not participate in the complex formation with macroheterocyclic receptors, may have applications in fields where strict control of molecular orientation at the interface is required, such as nanoelectronics, sensorics, catalysis, etc